Transferências de recursos federais do Sistema Único de Saúde para estados, distrito federal e municípios: Os desafios para a implementaç\~ao dos critérios da Lei Complementar no 141/2012 - Sérgio F. Piola (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This paper presents the challenges for the implementation of the intergovernmental transferring criteria established in Complementary Law 141, of January 2012, which regulates Constitutional Amendment No. 29, of 2000, for the Unified Health System (SUS). The Law establishes norms for a resource allocation that aims the reduction of regional disparities, old demand of this sector's researchers. This new model of financial resources allocation requires a shift in the logic that has driven the federal resources allocation on health sector in Brazil, furthermore it implies structural changes in the distribution patterns applied by the Ministry of Health.
Keywords: I18; 330; public health; government expenditures; financial resources allocation